Profil pH dan Volatile Suspended Solids pada Proses Pengomposan Tandan Kosong Kelapa Sawit Menggunakan Pupuk Cair Organik Aktif sebagai co-Composting - Trisakti, Bambang; Pranatha Sijabat, Irvan (Talenta Publisher (Universitas Sumatera Utara), 2020)
Oil Palm Empty Fruit Bunches (OPEFB) from the palm oil processing industry is discharged to the final processing site without any use. OPEFB can be used as raw material for composting by adding active organic liquid fertilizer (ALOF). This study aims to determine the composter design of pH and volatile suspended solids (VSS) by varying the capacity of the composter so that good quality compost is produced. The composting process is done by cutting oil palm empty fruit bunches with a size of 1-3 cm then put into the composter with a capacity variations of 2, 5 and 10 kg and added active organic liquid fertilizer to reach the optimum moisture content (MC) value of 55-65%. The results of the analysis are compared with SNI 19-7030-2004. The parameters analyzed during composting are pH and VSS. The results of composting that meet the compost criteria based on SNI 19-7030-2004 are composter capacity of 5 kg, where the results obtained during composting are pH 7.5 and VSS 211.640 mg/L.